Improving Students’ Critical Thinking Skills Through Virtual Laboratory Based Problem- Solving Scenarios - Nurul Fitiyah; Cici Madiyawati; Malini Putri Dwiyanti; Gunawan Gunawan; Nina Nisrina (Indonesian Journal of STEM Education, 2023)
Critical thinking skills are essential competencies in 21st-century physics education. However, previous studies indicate that students’ critical thinking abilities remain relatively low due to teacher-centered instructional practices and limited exploratory learning experiences. This article aims to systematically review the effectiveness of implementing virtual laboratory-based problem-solving scenarios in improving students’ critical thinking skills, particularly in Ohm’s Law material. The study employed a literature review method by analyzing relevant national and international journal articles published within the last ten years. The selected articles met criteria related to topic relevance, research methodology, and examined variables. The findings reveal that the integration of virtual laboratories and problem-solving approaches consistently contributes to improving students’ analytical skills, evaluation abilities, logical reasoning, and conclusion drawing. Interactive simulations and structured problem-solving stages enhance students’ active engagement and higher-order thinking skills. Therefore, virtual laboratory-based problem-solving scenarios are recommended as an innovative instructional strategy in physics learning.